RNA Sequencing Reveals Diverse Functions of Amniotic Fluid Neutrophils and Monocytes/Macrophages in Intra-Amniotic Infection - Nardhy Gomez-Lopez; Roberto Romero; Aneesha Varrey; Yaozhu Leng; Derek Miller; Bogdan Done; Yi Xu; Gaurav Bhatti; Kenichiro Motomura; Meyer Gershater; Roger Pique-Regi; Adi L. Tarca (Karger Publishers, 2020)
Intra-amniotic infection, the invasion of microbes into the amniotic cavity resulting in inflammation, is a clinical condition that can lead to adverse pregnancy outcomes for the mother and fetus as well as severe long-term neonatal morbidities. Despite much research focused on the consequences of intra-amniotic infection, there remains little knowledge about the innate immune cells that respond to invading microbes. We performed RNA-seq of sorted amniotic fluid neutrophils and monocytes/macrophages from women with intra-amniotic infection to determine the transcriptomic differences between these innate immune cells. Further, we sought to identify specific transcriptomic pathways that were significantly altered by the maternal or fetal origin of amniotic fluid neutrophils and monocytes/macrophages, the presence of a severe fetal inflammatory response, and pregnancy outcome (i.e., preterm or term delivery). We show that significant transcriptomic differences exist between amniotic fluid neutrophils and monocytes/macrophages from women with intra-amniotic infection, indicating the distinct roles these cells play. The transcriptome of amniotic fluid immune cells varies based on their maternal or fetal origin, and the significant transcriptomic differences between fetal and maternal monocytes/macrophages imply that those of fetal origin exhibit impaired functions. Notably, transcriptomic changes in amniotic fluid monocytes/macrophages suggest that these immune cells collaborate with neutrophils in the trafficking of fetal leukocytes throughout the umbilical cord (i.e., funisitis). Finally, amniotic fluid neutrophils and monocytes/macrophages from preterm deliveries display enhanced transcriptional activity compared to those from term deliveries, highlighting the protective role of these cells during this vulnerable period. Collectively, these findings demonstrate the underlying complexity of local innate immune responses in women with intra-amniotic infection and provide new insights into the functions of neutrophils and monocytes/macrophages in the amniotic cavity.